SISTEM KEAMANAN BRANKAS DENGAN RFID DOOR LOCK BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN CISCO PACKET TRACER - -, Amirah -; Talakua, Prisilia; -, Opitasari -; -, Fitria - (TRANSFORMASI, 2025)
The development of Internet of Things (IoT) technology has brought significant transformations in various fields, including security systems in securing valuable assets, such as safes, which require a high level of security. The purpose of this study is to design and implement a safe security system based on RFID and IoT, simulate the system using Cisco Packet Tracer to ensure its functionality and evaluate the effectiveness of the system in securing access to the safe. The system development model used is the ADDIE method which consists of five stages of development, namely; (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation. Problem analysis uses analysis and Feasibility Analysis uses TELOS analysis. The results of the System reliability analysis on this system are Verification Accuracy is 100% accurate in distinguishing valid and invalid tags based on data, while Response Speed is the response time between RFID reading and the door opening an average of 1 second. The system continues to run well as long as the server is active and the device is connected to the network. This research is expected to provide an alternative solution for an affordable and virtually simulated safe security system, as a reference or initial prototype for the development of a larger scale IoT security system and to demonstrate the potential use of Cisco Packet Tracer in RFID and IoT-based security system simulations.